Neopterin inhibits ATP-induced calcium release in alveolar epithelial cells in vitro - Georg Hoffmann; Frank Gollnick; Rainer Meyer (Mediators of Inflammation)
Background: Serum neopterin concentrations rise during activation of the cellular immune system. It is suggested that neopterin interacts with cellular redox mechanisms. This induces oxidative stress, which inhibits intracellular Ca2+ transients in various cell types. In type II alveolar epithelial cells, Ca2+ increase is considered involved in the exocytosis of surfactants. This exocytosis is disturbed during inflammation.